The Visual and Quantitative Study of the Microoccurrence of Irreducible Water at the Pore and Throat System in a Low-Permeability Sandstone Reservoir by Using Microcomputerized Tomography. (6th August 2018) - Gu, Xiaoyu; Pu, Chunsheng; Huang, Hai; Khan, Nasir; Liu, Jing; He, Yanlong; Jing, Cheng; Huang, Feifei; Qi, Aojiang
Abstract : The microflow equipment monitored with micro X-ray computerized tomography (CT) is employed to investigate the microoccurrence of the irreducible water in a low-permeability sandstone core. By means of image segmentation and the three-dimensional (3D) image reconstruction technique, the visual microdistribution characteristics of irreducible water in two-dimensional (2D) slices and the 3D pore-throat system are quantitatively evaluated. Some interesting findings are list as below. Firstly, due to the variant micro geometric structures of the pore-throat systems, specific core slices showed significantly different irreducible water saturation even though these slices had same areal porosity. Secondly, due to the influence of capillary trapping and the existence of oil-wetting clay (main chlorite), the irreducible water saturation in the throat system (64%) is much larger than that in the pore system (36%). Furthermore, the wetting phase (irreducible water) did not spread all over the surface of the pore-throat network which caused a much more complicated oil-water two-phase interface. Thirdly, in micro scale, the main irreducible water occurrence mode in the pore system is much different from that in the throat system. In the pore system, the irreducible water principally existed in the corner of the pores which are linked through a water film. While in the throat system, the irreducible water occurrence is dominated by the water film. However, 25.5% of the throats are blocked by the irreducible water which cut off the crude oil drainage channels.